Functional specialisation and working conditions in Europe - Roman Stöllinger; Sandra M. Leitner; Zuzana Zavarska (Hans-Böckler-Stiftung, 2023)
Specialisation in value-chain functions is one of the new phenomena introduced by global value chains and holds great potential for productivity gains. The advantages of global value chain integration, however, could be potentially countered by unfavourable functional specialisation. This study shows that functional specialisation in production activities ('fabrication') tends to hold back wages. For Central and East European EU member states, a specialisation as 'factory economies' could thus become a development trap.
urn:nbn:de:101:1-2023051610080068074709
Keywords: 330; GVC; FDI; social economy; global value chain